The influence of women empowerment on child nutrition in rural Nigeria - Salawu, M. B.; Rufai, A. M.; Salman, Kabir K.; Ogunniyi, Adebayo (African Economic Research Consortium, 2020)
In Nigeria, the low status of women and inflexible gender gaps contribute to weak dietary diversity and chronic child malnutrition. Child malnutrition is persistent,despite several interventions which fail to capture the need to empower women to improve the menace. In this study, the influence of women empowerment on child nutrition in rural Nigeria was therefore examined. Secondary data were sourced from General Household Survey Panel 2015-2016. Data were analyzed using the descriptive statistics, Modified Women Empowerment Index, Ordinary Least Square regression and Instrumental Variables techniques to correct for potential endogeneity. The result shows that majority (over 90%) of the households consumed cereals, vegetables, oils and fat, and spices, condiments and beverages while the least consumed food groups were milk and milk products (36%) and eggs (11%). It was also found that on average, women had less than two empowerment indicators implying low empowerment among women. Meanwhile, women empowerment significantly increased the household dietary diversity and consequently reduces the probability of child stunting. Therefore, the findings from this study lend support to the claims that woman empowerment remains a pathway out of cycle of weak dietary diversity and consistence child malnutrition in rural Nigeria.